Hubungan Pola Makan, Aktivitas Fisik, dan Gangguan Menstruasi dengan Status Gizi Remaja Putri di SMAN 1 Tangerang Selatan - Azkaa Khairunnisa; Said, Irfan; Wikanti, Cita Zahra Ayu (Kabar Gizi Indonesia, 2023)
One of the groups that are vulnerable to nutritional problems is adolescents, especially adolescent girls, so that adolescents face many health and nutritional problems. Nutritional status in adolescents is generally influenced by dietary factors, physical activity habits, and menstrual disorders. The purpose of this study was to determine the relationship of diet, physical activity, and menstrual disorders to the nutritional status of adolescent girls at SMAN 1 South Tangerang. This study used a cross sectional study design. The sampling technique used purposive sampling with a total sample of 247 adolescent girls. Data were collected in the form of questionnaires and anthropometric measurements (weight and height). The statistical analysis used was the chi-square test. The results showed that there was no significant relationship between diet and nutritional status of adolescent girls (p-value = 0.931), there was no significant relationship between physical activity and nutritional status of adolescent girls (p-value = 0.871), there was no significant relationship between menstrual disorders and nutritional status of adolescent girls (p-value = 0.896). The conclusion in this study is that there is no relationship between diet, physical activity, and menstrual disorders with the nutritional status of adolescent girls.